2011
DOI: 10.1509/jmkr.48.spl.s150
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Complex Financial Products in Emerging Markets: Evidence from Rainfall Insurance in India

Abstract: Recent financial liberalization in emerging economies has led to the rapid introduction of new financial products. Lack of experience with financial products, low levels of education, and low financial literacy may slow adoption of these products. This article reports on a field experiment that offered an innovative new financial product, rainfall insurance, to 600 small-scale farmers in India. A customized financial literacy and insurance education module communicating the need for personal financial manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
106
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 25 publications
(20 reference statements)
2
106
0
2
Order By: Relevance
“…The prediction of De Nicola and Hill is in line with the findings of Clarke and Kalani (2011) 11 who indeed find that the demand for wealth is inverse U-shaped in the amount of wealth.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…The prediction of De Nicola and Hill is in line with the findings of Clarke and Kalani (2011) 11 who indeed find that the demand for wealth is inverse U-shaped in the amount of wealth.…”
supporting
confidence: 88%
“…Panel data designs based on 9 annual household surveys of adopters and non-adopters to study adoption and/or impact are 10 less frequently applied. Randomised control trials of commercial insurance products are, with 11 some exceptions, rarely used. However, it should be noted that more recent studies on 12 insurance are able to move beyond stated preferences by conducting field experiments.…”
mentioning
confidence: 99%
“…Early papers examined adoption decisions (Giné et al 2010) and barriers to adoption , and found that trust, price reductions, and, to a lesser extent, financial education (Gaurav, Cole and Tobacman 2011;Dercon et al 2014;Cai and Song 2013) can drive adoption. Robust demand-side complementarities with other financial products have not been found.…”
Section: Introductionmentioning
confidence: 99%
“…Wiedzę finansową można próbo-wać podnosić przez różne działania o charakterze edukacyjnym i w ten sposób stymulować popyt. Z przeprowadzonych eksperymentów wynika, że jest to skuteczne 49 . Warto tu zauważyć, że zaufanie i wiedza (finansowa) mogą być względem siebie substytucyjne.…”
Section: Wiedza Finansowaunclassified